Delegation of Governor Regulation in Ensuring Utility and Justice - Astariyani, Ni Luh Gede; Wairocana, I Gusti Ngurah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 8 No 3 (2019), 2019)
Delegation means delegation of authority to make Law and Regulations. Article 246 paragraph (1) of Act No. 23 of 2014 on Regional Government stipulates that “to implement the Regional Regulation or over the power of Law and Regulations, the Head of Region shall pass the Head of Region Regulation.” The words "implement" and "over the power" which contains ambiguity of command cause philosophical problem related to the validity value. It becomes a sociological problem if such delegation cannot predict the dynamics of society. Furthermore, it becomes a juridical problem due to the existence of vague norm which creates multi interpretation which could potentially miss the aim of delegation of regulation. Specifically, this article has specific aims to examine philosophically concerning the need for delegations of authority to regulate, examine and find the direction of regulation in the delegation of regulation to governor regulation in ensuring utility and justice. This is a normative legal research with literature study which employs statute, philosophy, theories, conceptual and contextual approaches. The study so that with regard to the philosophical basis, delegation of regulation to Governor Regulation is needed to formulate technical and detail norms, the urgent factor contained herein as well as brief discussion and The direction of regulation to the Governor Regulation in the Regional Government Act to implement Regional Regulation or over the power of law and regulations. Such direction is based on command from the higher law and regulations, or established based on delegation.